A new Typhlocharis (Coleoptera: Carabidae: Anillina) from Spain: combining adult and larval morphological data with DNA information - Andújar, Carmelo; Grebennikov, Vasily V.; Lencina, José Luís; Serrano, José (Zootaxa, 2010)
Adult and larva of Typhlocharis toletana n. sp. (Coleoptera: Carabidae: Anillini) are described from the province of Toledo, Central Spain. Identical mitochondrial cox1 gene haplotype suggested that the adults and larvae are conspecific. Typhlocharis toletana is the third species of the genus with an unguiform shape of gonocoxite 2 of the ovipositor, a character state that is considered as ancestral. However, T. toletana is not closely related to the other two species having a similarly shaped gonocoxite 2, as judged by their morphological characters and geographic distribution. It is concluded that this ancestral state has been kept in different lineages within Typhlocharis. Species relationships inferred from a preliminary molecular analysis of five Typhlocharis taxa are not congruent with putative morphological lineages. Finally, it was found that the larva of T. toletana is morphologically indistinguishable from that of Typhlocharis sp. described by Arndt et al. (1999).